Parental Communication and Intrafamily Violence in Community Mental Health Adolescents - Álvarez Apaza, Rosmery Anddy (2026)
Intrafamily violence in adolescents is a community mental health concern with negative consequences for well-being and psychosocial adjustment. This study aimed to determine the association between parental communication and intrafamily violence among adolescents receiving care at a Community Mental Health Center in southern Peru. A quantitative, cross-sectional, correlational study was conducted with 100 adolescents aged 12 to 18 years treated at the San Miguel Arcángel Community Mental Health Center (Juliaca). The Parent–Adolescent Communication Scale (mother and father communication) and the Intrafamily Violence Questionnaire for Adolescents (overall violence and physical, psychological, and sexual dimensions) were administered. Pearson and Spearman correlations were computed depending on the distribution of the variables, with statistical significance set at p < 0.05. Results showed an inverse association between mother–adolescent communication and total intrafamily violence (r = -0.423; p < 0.001), as well as between father–adolescent communication and total violence (r = -0.381; p < 0.001). For physical violence, inverse associations were found with mother communication (r = -0.269; p = 0.007) and father communication (r = -0.284; p = 0.004). For psychological violence, mother communication was inversely related (rho = -0.366; p < 0.001), whereas father communication showed a positive association (rho = 0.426; p < 0.001). For sexual violence, mother communication was inversely associated (rho = -0.218; p = 0.029), with no significant association for father communication (rho = -0.106; p = 0.294). In conclusion, parental communication—particularly mother communication—was associated with lower intrafamily violence, highlighting its relevance for preventive interventions in community mental health settings.